Հոգու և կյանքի սկիզբ հասկացությունները ժողովրդական հավատալիքներում - Ա. Ս. Լաչինյան (ՀՀ ԳԱԱ հրատ.)
В народных поверьях понятия душа, дух и совесть часто отождествлялись. В силу сказанного искусственное прерывание беременности не считалось грехом и даже оправдывалось в тех случаях, когда душа и совесть идентифицировались, поскольку в стадии развития плод не наделен совестью. It is necessary to understand which stage of pregnancy is considered as a“threshold of life” for defining the abortions adepravity. Therefore, the issue is the perception of the fetus as a spiritual phenomenon. In the result of the study it was found out that people often classified the soul, and the conscience as one common phenomenon.
Keywords: Ethnography; Geography; Anthropology; Recreation; Folklore; History